2011
DOI: 10.1038/nsmb.2125
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the pre-miRNA structure by Drosophila Dicer-1

Abstract: Drosophila melanogaster has two Dicer proteins with specialized functions. Dicer-1 liberates miRNA-miRNA* duplexes from precursor miRNAs (pre-miRNAs), whereas Dicer-2 processes long double-stranded RNAs into small interfering RNA duplexes. It was recently demonstrated that Dicer-2 is rendered highly specific for long double-stranded RNA substrates by inorganic phosphate and a partner protein R2D2. However, it remains unclear how Dicer-1 exclusively recognize pre-miRNAs. Here we show that fly Dicer-1 recognizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
164
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(183 citation statements)
references
References 52 publications
14
164
0
2
Order By: Relevance
“…5 The discrepancies in the above, reported substrate preferences of hDicer and Dcr-1 may be due to genuine differences between the two enzymes, different assay conditions, and/or different substrates used in the studies. Previous work examined a small number of arbitrarily selected pre-miRNAs and their mutants as Dicer substrates (e.g., Ma et al 2008;Chakravarthy et al 2010;Zhang and Zeng 2010;Park et al 2011;Starega-Roslan et al 2011;Tsutsumi et al 2011). The human genome encodes hundreds of miRNA genes, and the predicted pre-miRNAs vary greatly in the end structure, stability and length of the duplex region, and size of the terminal loop.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The discrepancies in the above, reported substrate preferences of hDicer and Dcr-1 may be due to genuine differences between the two enzymes, different assay conditions, and/or different substrates used in the studies. Previous work examined a small number of arbitrarily selected pre-miRNAs and their mutants as Dicer substrates (e.g., Ma et al 2008;Chakravarthy et al 2010;Zhang and Zeng 2010;Park et al 2011;Starega-Roslan et al 2011;Tsutsumi et al 2011). The human genome encodes hundreds of miRNA genes, and the predicted pre-miRNAs vary greatly in the end structure, stability and length of the duplex region, and size of the terminal loop.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster expresses two Dicer isoforms, with Dicer-1 (Dcr-1) being responsible for the processing of pre-miRNAs, and Dicer-2 for long dsRNAs (Lee et al 2004). Tsutsumi et al (2011) reported that Dcr-1 selects the correct substrates by measuring the distance between the terminal loop and the 2-nt 39 overhang of a pre-miRNA. Extending the stem region or reducing the loop size compromised the processing by Dcr-1, seemingly consistent with the findings with hDicer (Ma et al 2008;Chakravarthy et al 2010;Zhang and Zeng 2010), even though the same study also showed that hDicer did not discriminate against such different RNA substrates (Tsutsumi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following export into the cytoplasm, pre-miRNA are cleaved by Dicer-1 to generate mature miRNA, which are then loaded onto an Ago1-dependent RNA-induced silencing complex (RISC) [56][57][58] . As in mammals, Drosophila Ars2 (dArs2) interacts with the CBC and Microprocessor, and is required for pri-miRNA processing and stability [49] .…”
Section: Ars2/serrate and Microrna Biogenesismentioning
confidence: 99%
“…In its native conformation, the region of the sponge LSU from which REm-1 derives does not form the type of secondary structure required for recognition by the canonical miRNA biogenesis machinery , Zeng et al 2005, Han et al 2006, Tsutsumi et al 2011. Furthermore, secondary structure analysis of the regions flanking REm-1 shows that the formation of such a structure is unlikely even from a fragmented LSU (Figure 5.3).…”
Section: Biogenesis Of Rem-1mentioning
confidence: 99%